Servant leadership, Organization Commitment and Job Satisfaction on Organizational Citizenship Behaviour - Ratna Syaka Aprilda; Dian Alfia Purwandari; Tantri Yanuar Rahmat Syah (Penerbit Kemala Indonesia, 2019)
This study aimed to analyze the effect of Servant leadership, Organizational Commitment and Job Satisfaction on Organizational Citizenship Behaviour. Here, the influence of Servant leadership and Organizational Commitment on Job Satisfaction need to assessed to obtain Organizational Citizenship Behaviour. In this study, we collect the data from civil servants people with 196 respondents using the random probability sampling method. The descriptive research analysis model with Partial Least Square (PLS) using Smart PLS software was used in this study. The results show that a Servant leadership, Organizational Commitment and Job Satisfaction had a positive effect on employee organizational citizenship behaviour. It can be concluded that the better Servant Leadership, Organizational Commitment and Job Satisfaction, the greater the organizational citizenship behaviour of employees is reflected in the actions of employees with Servant Leadership on Job Satisfaction as the most significant value.